Asstech Application Based E-Learning System to Improve The Quality Of 21st Century Inclusive Education - Miftahol Jannah; Arfan Muammar; Eni Fariyatul Fahyuni (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2019)
This study aims to describe digital optimization E-learning system based on "ASSTECH" to improve the quality of 21st century Inclusive education. E-Learning system is an effort digital to facilitate the learning process and strengthening values in each subject to students who have special needs. In the context of inclusive education, E-learning systems based on Asstech adjusted to the characteristics and needs of students, such as JAWS functions to change text into sound, i-CHAT to help strengthen hearing, websites and other learning media designed for students with special needs. This study uses a qualitative approach that seeks to obtain and collect and process, analyze and define data qualitative. The qualitative approach in this research various library sources such as prociding papers, journals, newspapers or magazines, reference books and so on which are then constructed as a critical thinking framework so that this approach is expected able to provide accurate about E-Learning Based Learning Technology "Asstech" in improving the quality of 21st century inclusive education. Keywords: e-learning system; ASSTECH; inclusive education.